Application of the categorization method to assess the maturity of processes on the example of the risk management proces - Domańska-Szaruga, Beata; Wereda, Wioletta (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
The purpose of the study is to present a proposal for a method of the assessing the maturity of processes in an organization based on the author’s model of process maturity of the risk management in the offices of local government units in Poland. The results of studies on the process maturity of the risk management in the units were also presented. The research was conducted in 2018 with the in-depth interview method and developed by using the categorization method. The results of the research were presented synthetically in a graphic manner, while in conclusions the practical application of the presented proposal was pointed out.